EFFECTS OF DIFFERENT HYDROPONIC SUBSTRATE COMBINATIONS AND WATERING REGIMES ON PHYSIOLOGICAL AND ANTI-FUNGAL PROPERTIES OF SIPHONOCHILUS AETHIOPICUS - Xego, S.; Kambizi, L.; Nchu, F (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Production of medicinal plants in controlled environments, particularly hydroponic technology, provides opportunities for high quality biomass accumulation and optimizes production of secondary metabolites. Applying special watering regimes in combination with efficient soil draining is an encouraging new tool for the production of pharmaceutical relevant plants. The purpose of this paper was to evaluate the effect of substrate combinations and watering regimes on nutrient uptake, anti-F. oxysporum activity and secondary metabolite profile of S. aethiopicus. Materials and Methods: Coir was used as the main component for the preparation of media in different combinations; T1 (Coir + vermiculite + perlite + bark), T2 (Coir + bark), T3 (Coir + perlite) and T4 (Coir + vermiculite). Plants in different treatments were grown under two watering regimes: 3 and 5-days watering intervals. At 9 weeks post treatment, plants were harvested, oven dried and tissue nutrient content, anti-F. oxysporum activity and secondary metabolites were analyzed. Results: The results showed that there were significant differences (P < 0.05) on the uptake of P, K, N, Mg, Fe, Cu, B and NH4-.The highest mean values for most nutrients were obtained in treatments under 3-days interval. Acetone extracts of S. aethiopicus under 5-days interval were the most bioactive against F. oxysporum. The MIC values obtained are relatively lower for the rhizomes, ranging from 0.078 - 0.3125 mg/ml compared to the higher MIC values (0.375 - 0.75 mg/ml) obtained in the leaves. LC-MS analysis of acetone extracts revealed the presence of phytochemicals such as caffeic acid, quercetin, p-hydroxybenzoic acid, rutin, kaempferol, epicatechin, naringenin, hesperetin and protocatechuic acid. Conclusion: The antimicrobial activity and/or the phytochemical profile of the crude extracts were affected by watering regimes.